2001
DOI: 10.1128/jb.183.18.5441-5444.2001
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of Biphenyl Dioxygenase: Emergence of Enhanced Degradation Capacity for Benzene, Toluene, and Alkylbenzenes

Abstract: Biphenyl dioxygenase (Bph Dox) catalyzes the initial oxygenation of biphenyl and related compounds. Bph Dox is a multicomponent enzyme in which a large subunit (encoded by the bphA1 gene) is significantly responsible for substrate specificity. By using the process of DNA shuffling of bphA1 of Pseudomonas pseudoalcaligenes KF707 and Burkholderia cepacia LB400, a number of evolved Bph Dox enzymes were created. Among them, an Escherichia coli clone expressing chimeric Bph Dox exhibited extremely enhanced benzene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…In particular, it is noteworthy that an Escherichia coli clone carrying pSHF1072 plasmid exhibits wide and enhanced capabilities to degrade not only alkylbenzenes but also benzene and toluene, compounds that are rarely attacked by wild-type KF707 Bph Dox. 8) Sequence analysis of the pSHF1072 bphA1 gene revealed that four amino acids (His255Gln, y To whom correspondence should be addressed. Tel/Fax: +81-29-861-6733; E-mail: suenaga-hikaru@aist.go.jp * Present address: Fuji Gotemba Research Labs, Chugai Pharmaceutical Co., Ltd., Gotemba 412-8513, Japan Abbreviations: Bph Dox, biphenyl dioxygenase; PCB, polychlorinated biphenyl; MOPS, 4-morpholinepropanesulfonic acid; MEG, 50 mM MOPS buffer pH 7.0, containing 5% ethanol and 5% glycerol Val258Ile, Gly268Ala, and Phe277Tyr) were changed from KF707 BphA1 to those in the LB400 BphA1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is noteworthy that an Escherichia coli clone carrying pSHF1072 plasmid exhibits wide and enhanced capabilities to degrade not only alkylbenzenes but also benzene and toluene, compounds that are rarely attacked by wild-type KF707 Bph Dox. 8) Sequence analysis of the pSHF1072 bphA1 gene revealed that four amino acids (His255Gln, y To whom correspondence should be addressed. Tel/Fax: +81-29-861-6733; E-mail: suenaga-hikaru@aist.go.jp * Present address: Fuji Gotemba Research Labs, Chugai Pharmaceutical Co., Ltd., Gotemba 412-8513, Japan Abbreviations: Bph Dox, biphenyl dioxygenase; PCB, polychlorinated biphenyl; MOPS, 4-morpholinepropanesulfonic acid; MEG, 50 mM MOPS buffer pH 7.0, containing 5% ethanol and 5% glycerol Val258Ile, Gly268Ala, and Phe277Tyr) were changed from KF707 BphA1 to those in the LB400 BphA1.…”
mentioning
confidence: 99%
“…E. coli strain JM109 carrying pHSF1072 8) was grown at 37 C in 1 liter of Luria-Bertani medium containing 50 mg/ml ampicillin and 0.1 mM isopropyl--D-galactopyranoside (IPTG) from a 1% (v/v) seeding of an overnight preculture. After 12 h of incubation, the E. coli cells were harvested and suspended in a 50 mM MOPS buffer (pH 7.0) containing 5% ethanol and 5% glycerol (MEG).…”
mentioning
confidence: 99%
“…Mutants of toluene dioxygenase were generated by random and saturation mutagenesis that exhibited higher activity towards toluene and 4-picoline (Sakamoto et al, 2001). Mutants of biphenyl dioxygenases with enhanced substrate specificity and changed regioselectivity were obtained by random and site-directed mutagenesis and gene shuffling (Brühlmann & Chen, 1999;Erickson & Mondello, 1993;Suenaga et al, 2001). In this study, rational design was used in order to change the product spectra of TecA.…”
Section: Rational Engineering Of Tecamentioning
confidence: 99%
“…Because, the native strains grow very good and have advanced adaptability in particular geographical region [10]. native microorganisms are highly adaptable and have the capability to degrade the recalcitrant compounds through evolution of new genes, which encode enzymes that can use these compounds as their primary substrates [11].…”
Section: Introductionmentioning
confidence: 99%